Indian leather 2010 : a technology, industry, and trade forecast - Amudeswari, A.; Srinivasan, A. V. (Amruthur V.); Thyagarajan, G.; Technology Information, Forecasting, and Assessment Council (India); Central Leather Research Institute (India); Technology Assessment and Forecasting in Leather Sector (Project : Central Leather Research Institute, India) (Madras : Central Leather Research Institute, India, 1994)
Report of the Technology Assessment and Forecasting in Leather Sector, project organized by the Central Leather Research Institute (India), Madras.
"This study was sponsored by Technology Information Forecasting and Assessment Council (TIFAC), Department of Science and Technology, Government of India, New Delhi"--T.p. verso.
Mode of access: Internet.
Keywords: Leather industry and trade -- India -- Congresses